Salinity-Based Toxicity of CuO Nanoparticles, CuO-Bulk and Cu Ion to Vibrio anguillarum - Rotini, Alice; Tornambè, Andrea; Cossi, Riccardo; Iamunno, Franco; Benvenuto, Giovanna; Berducci, Maria T.; Maggi, Chiara; Thaller, Maria C.; Cicero, Anna M.; Manfra, Loredana; Migliore, Luciana (Frontiers in Microbiology, 2017)
Bacteria are used in ecotoxicology for their important role in marine ecosystems and their quick, reproducible responses. Here we applied a recently proposed method to assess the ecotoxicity of nanomaterials on the ubiquitous marine bacterium Vibrio anguillarum, as representative of brackish and marine ecosystems. The test allows the determination of 6-hour EC50 in a wide range of salinity, by assessing the reduction of bacteria actively replicating and forming colonies. The toxicity of copper oxide nanoparticles (CuO NPs) at different salinities (5-20-35 ‰) was evaluated. CuSO4 5H2O and CuO bulk were used as reference toxicants (solubility and size control, respectively). Aggregation and stability of CuO NP in final testing dispersions were characterized; Cu2+ dissolution and the physical interactions between Vibrio and CuO NPs were also investigated. All the chemical forms of copper showed a clear dose-response relationship, although their toxicity was different. The order of decreasing toxicity was: CuSO4 5H2O > CuO NP > CuO bulk. As expected, the size of CuO NP aggregates increased with salinity and, concurrently, their toxicity decreased. Results confirmed the intrinsic toxicity of CuO NPs, showing modest Cu2+ dissolution and no evidence of CuO NP internalization or induction of bacterial morphological alterations. This study showed the V. anguillarum bioassay as an effective tool for the risk assessment of nanomaterials in marine and brackish environments.